Intravascular Leiomyomatosis as a Rare Cause of Nonthrombotic Pulmonary Embolism - Julie Van Maercke; Anne-Sophie Van Rompuy; Willy Poppe; Tom Verbelen; Marion Delcroix; Catharina Belge (Case Reports in Vascular Medicine)
Intravascular leiomyomatosis (IVL) is a very rare condition. It is characterized by the proliferation of benign smooth muscle cells within vascular structures without invasion of these tissues. Symptoms depend on the site of origin and the extent of invasion. Rarely, this neoplasm is located in the inferior vena cava or in the pulmonary vasculature potentially causing symptoms of dyspnea, chest pain, or syncope. We report the case of a 53-year-old woman who was referred to our hospital with extensive pulmonary embolism comprising of a subtotal occlusion of the right pulmonary artery with extension into the left pulmonary artery. Due to persistent dyspnea (New York Heart Association class II) despite anticoagulation, after a six-week period, imaging was repeated and showed stable findings. As she was not responding to adequate anticoagulant therapy, intima sarcoma of the pulmonary artery was suspected, and a pulmonary endarterectomy (PEA) was performed. A smooth, white, intravascular mass was easily and completely removed. Analysis demonstrated a lesion consisting of cells without atypia, showing expression of alpha-smooth muscle actin (alpha SMA) and desmin with partial expression of estrogen receptor (ER) and progesterone receptor (PR), leading to the diagnosis of intravascular leiomyomatosis. The patient fully recovered. Complete surgical removal of the intravascular tumor is recommended to relieve symptoms and prevent possible complications. Clinicians have to be aware that in unresolved pulmonary embolism, nonthrombotic and rare causes, like an intima sarcoma or intravascular leiomyomatosis, should be considered.